Exploring the Nexus between Exchange Rate and Stock Price: A Case of Sri Lanka - Tharsika, K. (ISROSET, 2020)
Stock market and exchange rate play a dominant role in the economy of any country whether it is developed or developing countries. The regulatory board and Government have to pay attention on the stock market performance and exchange rate fluctuation because any minor change in them will affect the economy in several ways. Therefore, knowing the short-run and long-run causal relationship between the exchange rates and stock price is essential. This paper endeavors to discover the causal relationship between them by using the monthly data on All Share Price Index (ASPI) of the Colombo Stock Exchange and five exchange rates namely Euro, Indian Rupee, Japanese Yen, UK Sterling Pound and US Dollar for the periods from January 2005 to December 2019 in the empirical analysis. Augmented Dickey-Fuller unit root test shows that the variables are non-stationary at the level and become a stationary on the first difference. Even though all selected variables have the same integration order, neither variables are co-integrated based on the Johansen's Co- integration Test, and the Granger Causality Test reveals that no short-run causal relationships between both.
Keywords: Exchange Rate; All Share Price Index; Unit Root; Johansen’s Co-integration; Granger Causality